Formation of iddingsite veins in the martian crust by centripetal replacement of olivine: Evidence from the nakhlite meteorite Lafayette. (1st April 2015) - Lee, M.R.; Tomkinson, T.; Hallis, L.J.; Mark, D.F.
Abstract: The Lafayette meteorite is an olivine clinopyroxenite that crystallized on Mars ∼1300 million years ago within a lava flow or shallow sill. Liquid water entered this igneous rock ∼700 million years later to produce a suite of secondary minerals, collectively called 'iddingsite', that occur as veins within grains of augite and olivine. The deuterium/hydrogen ratio of water within these secondary minerals shows that the aqueous solutions were sourced from one or more near-surface reservoirs. Several petrographically distinct types of veins can be recognised by differences in their width, shape, and crystallographic orientation. Augite and olivine both contain veins of a very fine grained hydrous Fe- and Mg-rich silicate that are ∼1–2 μm in width and lack any preferred crystallographic orientation. These narrow veins formed by cementation of pore spaces that had been opened by fracturing and probably in response to shock. The subset of olivine-hosted veins whose axes lie parallel to (0 0 1) have serrated walls, and formed by widening of the narrow veins by interface coupled dissolution–precipitation. Widening started by replacement of the walls of the narrow precursor veins by Fe–Mg silicate, and a crystallographic control on the trajectory of the dissolution–precipitation front created micrometre-scale {1 1 1} serrations. The walls of many of the finely serrated veins were subsequently replaced by siderite, and the solutions responsible for carbonation of olivine also partially recrystallized the Fe–Mg silicate. Smectite was the last mineral to form and grew by replacement of siderite. This mineralization sequence shows that Lafayette was exposed to two discrete pulses of aqueous solutions, the first of which formed the Fe–Mg silicate, and the second mediated replacement of vein walls by siderite and smectite. The similarity in size, shape and crystallographic orientation of iddingsite veins in the Lafayette meteorite and in terrestrial basalts demonstrates a common microstructural control on water–mineral interaction between Mars and Earth, and indicates that prior shock deformation was not a prerequisite for aqueous alteration of the martian crust.